Innovation in Civics and History Learning Through Quizizz-Assisted Collaborative Inquiry to Strengthen In-Depth Learning in High School - Wulandari, Eka Mia; Jatiningsih, Oksiana (IKIP Widya Darma Surabaya, 2026)
Objective: This study was conducted to analyze the effectiveness of the collaborative inquiry learning model with the help of the Quizizz application in improving deep learning in integrated Civics and History learning in high school. The main focus of this study is the application of the collaborative inquiry learning model combined with the Quizizz application can improve deep learning in integrated Civics and History learning in high school. Based on this focus, the problem formulation in this study is how is the process of implementing the collaborative inquiry learning model with the help of the Quizizz application in integrated Civics and History learning in high school? The substance of this study focuses on describing the process of implementing the collaborative inquiry learning model with the help of the Quizizz application in integrated Civics and History learning in high school. Method: The research method used is mixed method among quantitative and descriptive and does not conduct hypothesis testing with a sample of 3 teachers, namely 1 Pancasila Education teacher and 1 History teacher. The sampling technique used purposive sampling. Data collection was carried out at State Senior High School 1 of Gedangan, East Java. Data collection techniques used questionnaires, interviews, and observations whose data results will be analyzed descriptively qualitatively. Results: The data obtained were analyzed using qualitative descriptive analysis techniques. The results showed that 1) the integration of Quizizz in the collaborative inquiry stage was able to increase student engagement. 2) strengthen conceptual understanding across subjects. 3) encourage analytical skills which are indicators of deep learning. Novelty: What is new in this study is This study offers novelty in the form of integrating the collaborative inquiry model with the Quizizz application in integrated Civics-History learning to strengthen students' deep learning. In contrast to previous studies that only used Quizizz as an evaluation medium, this study uses Quizizz as a medium for presenting inquiry-based material and a collaboration facilitator. In addition, this study introduces a cross-disciplinary learning design between PPKn and History, which has not been widely explored in the context of deep learning in secondary schools.